PENGARUH P3TIP (PROGRAM PEMBERDAYAAN PETANI MELALUI TEKNOLOGI DAN INFORMASI PERTANIAN) TERHADAP PERILAKU PETANI - Sari, Ade Rachmah; Sumantri, Ari Tresna; Sulaeni, Sulaeni (Jurusan Agribisnis Fakultas Pertanian Universitas Sultan Ageng Tirtayasa, 2017)
P3TIP is a Farmers Empowerment Program Through Technology and Information. This program is funded by the World Bank and other volunteers in order to improve the quality of agricultural human resources in Indonesia. This study aims to analyze the effect of P3TIP implementation on farmers behavior including changes in knowledge, attitude and skills of farmers in breeding of rice seed. This research is conducted in Panosogan Village and Sukaratu Village, Cikeusal District, Serang Regency, Banten. Data analysed by tabulation and wilcoxon. The respondents of this research is 35 respondent. The result of this research showed that P3TIP (Padra Seed Farming) Activity has been able to empower farmers in Cikeusal Sub-district represented by Panosogan Village and Sukaratu Village, Serang Regency optimally, because there are some changes, the changes are knowledge, skill and attitude. The value is about 1,96 / - 1.96 and Knowledge -5.093 / 5,093, Skills -5,170 / 5,170 and attitude -5,177.